Rethinking Campus Life New Perspectives on the History of College Students in the United States (Historical Studies in Education, 2018)
This edited volume explores the history of student life throughout the nineteenth and twentieth centuries. Chapter authors examine the expanding reach of scholarship on the history of college students; the history of underrepresented students, including black, Latino, and LGBTQ students; and student life at state normal schools and their successors, regional colleges and universities, and at community colleges and evangelical institutions. The book also includes research on drag and gender and on student labor activism, and offers new interpretations of fraternity and sorority life. Collectively, these chapters deepen scholarly understanding of students, the diversity of their experiences at an array of institutions, and the campus lives they built.